Adoption of PayLater among Digital Natives in Jakarta: The Role of TPB and Trust - Hilsya Faiqotul Innayah; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research uses a combination of the Theory of Planned Behavior (TPB) and the trust construct to investigate what variables impact consumers' intentions to utilize PayLater services. Partially Least Squares-Structural Equation Modeling (PLS-SEM) was used to undertake the quantitative cross-sectional design of the study. According to the results, users' intents to use PayLater are positively and significantly impacted by trust, but there is no significant association between attitude toward the action, subjective norms, and perceived behavioral control. These results indicate that users’ confidence in system security, data protection, and the reliability of service providers serves as the primary determinant of PayLater adoption. Therefore, this study concludes that trust plays a more decisive role than psychological and social factors in shaping users’ engagement with PayLater services. Consequently, PayLater providers should focus on enhancing transparency, strengthening security systems, and safeguarding user data to build trust and encourage sustainable service usage.